Hygienic assessment of microelementosis in primary school children living on geochemical territory - Kuzminov B.P.; Skaletska N.M. (Medičnì Perspektivi)
In this work we consider methods of solving urgent issues of prevention of violations of children’s health those who live in technologically contaminated areas. Content of pollutants in environmental objects of Sosnivka town as geochemical province was conducted. We made a comparative analysis of pre-pathological health indicators of children living on this territory, as well as "conditionally clean territory" by the elemental composition of children’s hair and blood content, intensity of lipid peroxidation and activity of antioxidant enzymes, parameters of physical development and condition of their actual nutrition. Correlations between exposure to toxicants of the environment and changes in the health of children was revealed. There was developed integrated scheme of measures for the prevention of technogenic microelementosis among children.